2021
DOI: 10.1007/s00402-021-04036-2
|View full text |Cite
|
Sign up to set email alerts
|

Imageless robotic handpiece-assisted total knee arthroplasty: a learning curve analysis of surgical time and alignment accuracy

Abstract: Introduction Robotic-assisted surgery techniques are increasing in total knee arthroplasty (TKA). One crucial point is the prolonged time of surgery. The primary objective of this study was to determine the learning curve necessary to minimize the time of surgery. The secondary objective was to evaluate the accuracy of the implant alignment when using an imageless robotic system for TKA. Materials and methods In a case–control study, the first 70 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
1
25
0
1
Order By: Relevance
“…Furthermore, postoperative coronal alignment parameters were all comparable between the groups. In addition to the numerous published studies on improved alignment accuracy in primary robotic-assisted knee arthroplasty in comparison to conventional TKA [ 12 , 19 , 23 , 26 , 31 ], this case series was able to demonstrate a comparable accuracy and outcome to robotic-assisted primary knee arthroplasty. Intraoperative control of component alignment and joint line restoration in revision arthroplasty is often a challenge due to further bone loss or loss of bony reference points after implant removal.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Furthermore, postoperative coronal alignment parameters were all comparable between the groups. In addition to the numerous published studies on improved alignment accuracy in primary robotic-assisted knee arthroplasty in comparison to conventional TKA [ 12 , 19 , 23 , 26 , 31 ], this case series was able to demonstrate a comparable accuracy and outcome to robotic-assisted primary knee arthroplasty. Intraoperative control of component alignment and joint line restoration in revision arthroplasty is often a challenge due to further bone loss or loss of bony reference points after implant removal.…”
Section: Discussionmentioning
confidence: 67%
“…Robotic-assisted UKA conversion to TKA and primary RA-TKA were both done with the image-less robotic system NAVIO TM (Smith & Nephew, London, UK) using the Journey II BCS prothesis. Primary RA-TKA was performed as described before [ 7 , 23 ]. In the following, the technique of robotic-assisted UKA conversion to TKA is described:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Liow et al 11 reported that rTKAs were associated with a more accurate restoration of the joint line with only 3.2% of outliers (defined as >5 mm deviation) compared to a 20.6% in the conventional group. Savov et al 30 reported an overall incidence of 11% outliers (8 cases out of 70; p = 0.002) when comparing NAVIO assisted TKA with conventional technique with a mean error from planned of 2±1.2° regarding HKA (p < 0.001), 1±0.8° regarding medial…”
Section: Advantages Of Robotic-assisted Technique Accuracy and Radiog...mentioning
confidence: 99%
“…However, their analysis revealed an inflection point after the initial seven cases, identifying an initial learning stage with mean 100 min per case and a proficiency stage with mean 67 min per case (p < 0.001). The learning curve associated with the same robotic system (NAVIO) was analyzed by Savov et al, 30 on two groups of 70 consecutive patients operated with robotic and conventional technique, respectively.…”
Section: Drawbacks Of Robotic-assisted Technique Learning Curvementioning
confidence: 99%